Polyimidazolium protects against an invasive clinical isolate of Salmonella Typhimurium - Mon, Khin K. Z. (2023)
Frequent outbreaks of Salmonella Typhimurium infection, in both animal and human populations and with the potential for zoonotic transmission, pose a significant threat to the public health sector. The rapid emergence and spread of more invasive multidrug-resistant clinical isolates of Salmonella further highlight the need for the development of new drugs with effective broad-spectrum bactericidal activities. The synthesis and evaluation of main-chain cationic polyimidazolium 1 (PIM1) against several Gram-positive and Gram-negative bacteria have previously demonstrated the efficacy profile of PIM1. The present study focuses on the antibacterial and anti-biofilm activities of PIM1 against Salmonella in both in vitro and in ovo settings. In vitro, PIM1 exhibited bactericidal activity against three strains of Salmonella at a low dosage of 8 μg/mL. The anti-biofilm activity of PIM1 was evident by its elimination of planktonic cells within preformed biofilms in a dose-dependent manner. During the host cell infection process, PIM1 reduces the extracellular bacterial load, which reduces adhesion and invasion to limit the establishment of infection. Once intracellular, Salmonella strains were tolerant and protected from PIM1 treatment. In a chicken egg infection model, PIM1 exhibited therapeutic activity for both Salmonella strains, using stationary-phase and exponential-phase inocula. Moreover, PIM1 showed a remarkable efficacy against the stationary-phase inocula of drug-resistant Salmonella by eliminating the bacterial burden in >50% of the infected chicken egg embryos. Collectively, our results highlight the potential for PIM1 as a replacement therapy for existing antibiotic applications on the poultry farm, given the efficiency and low toxicity profile demonstrated in our agriculturally relevant chicken embryo model.